Geographical characteristics of the Una-Sana mesoregion - Nezirović, Senada; Durmišević, Belma (Journal for Geography, 2021)
Last geographically relevant attempt of adequate territorial differentiation of Bosnia and Herzegovina, based on the principles of complex geographical homogeneity,represents geographical regionalisation into four macroregional units: Peripannonian, Mountain-valley,macroregion of Bosnian and Herzegovinian high karst and Mediterranean macroregion. This paper particularly focused on geographical characteristics of onepart of Peripannonian macroregion–the Una-Sana mesoregion. Natural geographical characteristics are elaborated,such as geographical position, geological composition and structure, geomorphological,hydrogeographical, climate, pedological and biogeographical characteristics, including also social geographical characteristics such as number of population, density, structure of population and economy. According to a field research, former findings, previously collected various information and documents, this paper inclines to present basic characteristics of this region of Bosnia and Herzegovina, pointing out certain problems that Una-Sana mesoregion faces with, specially the„white plague“, as a negative natural change and big emigration of population.